Childhood traumatic events and loss of control eating in pregnancy: Findings from a community sample of women with overweight and obesity. (August 2021) - Emery, Rebecca L.; Benno, Maria Tina; Kleih, Theresa; Bell, Elizabeth; Mason, Susan M.; Levine, Michele D.
Abstract: Although eating disorder symptoms generally decrease in pregnancy, loss of control eating (LOC), defined by the consumption of food accompanied by a sense of being unable to control what or how much is eaten, often persists and may develop in pregnancy. Given that LOC is associated with higher weight status and psychological distress, it is important to understand factors associated with perinatal LOC. Although childhood traumatic events have been linked to LOC in non-pregnant women, the impact of such events on LOC in pregnancy is unknown. Accordingly, the present study aimed to examine the association between a history of childhood traumatic events and LOC prior to and during pregnancy among a community sample of pregnant women with overweight or obesity. Pregnant women ( N = 244) were enrolled in a longitudinal study. Women completed interviews between 12 and 20 weeks gestation to document a history of childhood traumatic events and the presence of LOC in the three months prior to and during their current pregnancy. Women were assessed for LOC monthly for the remainder of pregnancy. Results from a multinomial regression model showed that women with a history of childhood traumatic events had higher odds of engaging in LOC both prior to and during pregnancy (OR = 2.52, 95% CI [1.13, 5.64], p = 0.02) but not during pregnancy only (OR = 1.58, 95% CI [0.87, 2.89], p = 0.39). These findings indicate that women with a history of childhood traumatic events may be especially prone to LOC in the months prior to conception that continues throughout pregnancy. Highlights: Over 42% of women reported exposure to at least one traumatic event in childhood. Nearly 38% of women reported engaging in LOC during pregnancy. Childhood traumatic events increased the odds of LOC prior to and during pregnancy.